First-second degree statistics-based genetics of powdery mildew and yield attributing traits in blackgram (Vigna mungo) - M, BORAIAH K; BYREGOWDA, M; KEERTHI, C M; RAMESH, S; SINGH, CHANDU; SINGH, RAJIV K; S, BASAVARAJ P (The Indian Journal of Agricultural Sciences, 2022)
Genetics of yield related traits and powdery mildew disease (PMD) resistance unraveled using the combination of first and second degree of statistics in blackgram [Vigna mungo (L.) Hepper]. Eight crosses, their parents, F2 and F3 generations were evaluated for six yield attributing traits and PMD during kharif 2016 and rabi 2016–17 respectively. The first degree statistics suggested the predominance of genes with dominance effects, whereas second degree statistics revealed the additive gene effects in controlling most investigated traits. However, combination of first and second degree statistics revealed significant but lower magnitude of additive genetic effects [d] coupled with large additive genetic variance (σ2 A) for plant height and seed yield/plant in all six crosses, indicating the dispersion of increasing and decreasing effecting genes between parents. The estimates of σ2 A were considerably high for percent disease index (PDI) in all three crosses. Conversely, higher estimates of [d] and smaller estimates of σ2 A indicated small effect additive genes controlling days to 50% flowering, days to maturity and 100 seed weight in all the six crosses. Hence, unraveling the genetics based on both first and second degree statistics provide the comprehensive information on gene action involved in governing PMD resistance and yield attributing traits in blackgram, which helps in deciding efficient selection strategies to be followed for enhancing genetic gain.